Monte Carlo Simulation of the Adsorption of Binary Gas Mixtures on Heterogeneous Surfaces - F. Bulnes; A.J. Ramirez-Pastor; G. Zgrablich (Adsorption Science & Technology, 2005)
The adsorption of a gaseous mixture containing particles A and B was studied via lattice-gas simulations on homogeneous and heterogeneous bivariate surfaces characterized by a chessboard topography of strong and weak adsorbing sites. The effects of lateral interactions among adsorbed particles and of heterogeneity on the adsorption isotherms and differential heats of adsorption were analyzed. The results displayed a rich variety of behaviours and their analysis contributes to the understanding of mixed-gas adsorption at a molecular level.